Java in a nutshell : - Flanagan, David (O'reilly, 1997)
The bestselling Java in a Nutshell has been updated to cover Java 1.1. If you're a Java programmer who is migrating to 1.1, this second edition contains everything you need to get up to speed on the new features of Java 1.1. Or if you are just now jumping on the Java bandwagon, Java in a Nutshell still has all of the features that have made it the Java book most often recommended on the Internet. An advanced introduction to Java for C and C++ programmers teaches you everything you need to know about the language, while the complete quick-reference contains descriptions of all of the classes in the Java 1.1 API, with the exception of the Enterprise APIs.